Optimalisasi Fungsi Masjid melalui Gerakan Bersih-Bersih Berbasis Literasi Islam Digital di Desa Pojok Tulungagung - Baro'ah El-Chamdani; Misbakhul Khaer; Muchamat Amarodin (Journal of Innovation and Contribution to Community Service, 2026)
The Community Service Program (PKM) aims to address the low level of collective awareness among the community in maintaining mosque cleanliness, which has resulted in the suboptimal functioning of the mosque as a center for worship, social activities, and Islamic education in Pojok Village, Ngantru District, Tulungagung Regency. The PKM activities were carried out through a mosque clean-up movement integrated with the strengthening of Islamic literacy and mosque-based digital literacy. The method employed was Participatory Action Research (PAR), consisting of participatory observation, collaborative planning, the implementation of collective actions, mentoring, and reflective evaluation involving mosque management (takmir), mosque youth, religious leaders, and the general congregation. The results of the program indicate a significant improvement in the physical cleanliness of the mosque, the growth of community awareness and shared responsibility in maintaining cleanliness, and the strengthening of the culture of mutual cooperation and Islamic brotherhood (ukhuwah Islamiyah). Furthermore, the activities encouraged active participation from the younger generation, enhanced community understanding of cleanliness as a core value in Islamic teachings, and supported the optimization of the mosque as a center for Islamic and digital literacy. Overall, this PKM program offers a participatory and sustainable mosque-based community empowerment model that has a positive impact on spiritual, social, educational, and environmental aspects..